Different responses of ecosystem carbon exchange to warming in three types of alpine grassland on the central Qinghai–Tibetan Plateau. Issue 3 (30th December 2017) - Ganjurjav, Hasbagan; Hu, Guozheng; Wan, Yunfan; Li, Yue; Danjiu, Luobu; Gao, Qingzhu
Abstract: Climate is a driver of terrestrial ecosystem carbon exchange, which is an important product of ecosystem function. The Qinghai–Tibetan Plateau has recently been subjected to a marked increase in temperature as a consequence of global warming. To explore the effects of warming on carbon exchange in grassland ecosystems, we conducted a whole‐year warming experiment between 2012 and 2014 using open‐top chambers placed in an alpine meadow, an alpine steppe, and a cultivated grassland on the central Qinghai–Tibetan Plateau. We measured the gross primary productivity, net ecosystem CO2 exchange (NEE), ecosystem respiration, and soil respiration using a chamber‐based method during the growing season. The results show that after 3 years of warming, there was significant stimulation of carbon assimilation and emission in the alpine meadow, but both these processes declined in the alpine steppe and the cultivated grassland. Under warming conditions, the soil water content was more important in stimulating ecosystem carbon exchange in the meadow and cultivated grassland than was soil temperature. In the steppe, the soil temperature was negatively correlated with ecosystem carbon exchange. We found that the ambient soil water content was significantly correlated with the magnitude of warming‐induced change in NEE. Under high soil moisture condition, warming has a significant positive effect on NEE, while it has a negative effect under low soil moisture condition. Our results highlight that the NEE in steppe and cultivated grassland have negative responses to warming; after reclamation, the natural meadow would subject to loose more C in warmer condition. Therefore, under future warmer condition, the overextension of cultivated grassland should be avoided and scientific planning of cultivated grassland should be achieved. Abstract : Warming significantly stimulated carbon assimilation and emission in the alpine meadow, but net C uptake declined in the alpine steppe and the cultivated grassland. In cultivated grassland, decrease in gross carbon uptake and increase in soil respiration resulted in significant decrease in NEE under warming.